Mechanisms of Placebo Pain Reduction: An Empirical Investigation - Montgomery, Guy; Kirsch, Irving (Psychological Science, 1996)
Identical experimental pain stimuli were applied to the right and left index fingers of 56 university students, following the application of a placebo in the guise of a topical anesthetic to one of the fingers The pain stimuli were administered simultaneously to treated and untreated fingers for half of the subjects and sequentially for the others Significant and equivalent reductions in pain were reported in both conditions as a function of placebo administration These data indicate that reductions of experimental pain produced by placebos presented in the guise of local anesthetics are not mediated by such global mechanisms as anxiety reduction or the release of endogenous opioids